Robotic Resection of Gallbladder Cancer: A Single-Center Retrospective Comparative Study to Open Resection. Issue 4 (April 2023) - Tschuor, Christoph; Pickens, Ryan C.; Isenberg, Erin E.; Motz, Benjamin M.; Salibi, Patrick N.; Robinson, Jordan N.; Murphy, Keith J.; Iannitti, David A.; Baker, Erin H.; Vrochides, Dionisios; Martinie, John B.
Background: Minimally invasive surgery is gaining support for resection of gallbladder cancer (GBC). This study aims to compare operative and early outcomes of robotic resection (RR) to open resection (OR) from a single institution performing a high volume of robotic HPB surgery. Methods: Twenty patients with GBC underwent RR from January 2013 to August 2019. Outcomes were compared to a historical control of 23 patients with OR. Radical cholecystectomy for suspected GBC and completion operations for incidental GBC after routine cholecystectomy were both included. Results: Robotic resection had lower blood loss compared to OR (150 vs 350 mL, P = .002) and shorter postoperative length of stay (2.5 vs 6 days, P < .001), while median operative time was similar (193 vs 208 min, P = .604). There were no statistical differences in 30-day major complications or readmissions. No 30-day mortalities occurred. There was no statistical difference in survival trend ( P = .438) or median lymph node harvest (5 vs 3, P = .189) for RR compared to OR. Conclusion: Robotic resection of GBC is safe and efficient, with lower length of hospital stay and blood loss compared to OR. Technical benefits of robotic-assisted surgery may prove advantageous though larger studies are still needed.